The effect of Ibuprofen on female and male reproduction of the open thelyca marine shrimp, Litopenaeus - Alfaro-Montoya, Jorge (2013)
A research was designed to explore the effect of ibuprofen (IBU) as an intervening agent for prostaglandin biosynthesis on male and female reproduction of three species of Litopenaeus. Ovarian maturation was studied in L. stylirostris and L. vannamei injected periodically with IBU at 0.01 and 0.1 μg g-1 body weight (b.w.) and treated for unilateral eyestalk ablation. IBU at 0.1 μg induced a statistically (P < 0.05) higher rate of L. vannamei females with developing ovaries (45 ± 19%) as compared with controls (12 ± 8%) during 5 weeks; L. stylirostris did not activate vitellogenesis under this experimental protocol. IBU was also evaluated for male sexuality in L. occidentalis, L. stylirostris and L. vannamei. Periodic injections of IBU had no effect on sperm counts and spermatophore weights; however, sperm abnormalities in IBU 0.1 μg treated L. occidentalis and L. stylirostris were very low. In L. stylirostris, the renovation of normal spermatophores was remarkably improved in IBU treated males as compared with controls, but in L. vannamei spermatophore deterioration was not affected. The findings of this research support the hypothesis that prostaglandins are involved in penaeid reproduction playing a negative physiological role; however, altered steroidogenic pathways could also be involved